An in-depth investigation of a Pacific young people's eating habits and dietary diversity as related to the pathways of obesity : a thesis presented in the partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Auckland, New Zealand - Deo, Nikita Natasha (Massey University, 2014)
Background: Prevalence of obesity is high amongst Pacific youth aged 6-24 years. To understand obesity amongst Pacific youth, exploration into their social realities, culture, diet quality and food habits is needed. Aim: To explore dietary diversity and eating habits as well as cultural factors that influence food consumption of Pacific youth aged 16-24 years using a qualitative approach. Methodology: A sample of 30 Pacific youth was purposively selected. Diet quality was assessed using a newly developed dietary diversity questionnaire specific to Pacific people, based on guidelines from the FAO. Eating habits, meal patterns, food choices and related cultural and social influences was explored using a qualitative face-to-face interview. Results: Dietary diversity scores (DDS) were calculated by counting the number of established food groups (total of 26 food groups divided into 15 nutritious and 11 discretionary food groups). Food variety scores (FVS) were calculated by counting the number of individual food items consumed (n=227 foods in total; 129 nutritious foods and 98 discretionary foods) as well as within each food group. The eating habits data was analysed using a content analysis approach where trends in meal patterns, consumption at social occasions and weight status were identified. Dietary diversity: the mean total DDS was 23.1; the mean DDS of nutritious and discretionary food groups was 14.3 and 8.83 respectively. The mean total FVS was 91, the mean FVS of the nutritious and discretionary foods was 51.7 and 39.3 respectively. The most variety in the nutritious category was identified in the Vitamin A and Vitamin C rich fruit and vegetable groups, however, only moderate amounts of food items were consumed from these groups. The most variety in the discretionary category was identified in the drinks group where intakes ranged between four and ten items out of a total 14 identified items. Eating habits: a two-meals/day pattern was observed, with over half the participants skipping breakfast and consuming snacks during the day. For sixteen participants, their food intake increased due to the availability of a large variety of freely available food in their social environments. Weight: over half (57%) of the participants were unhappy with their weight and many of these participants have tried diet and exercise to manage their weight. Many participants perceived their unhealthy lifestyles to be the cause of overweight and obesity. Conclusion: dietary diversity was high amongst Pacific youth, however, the variety of nutritious foods consumed were moderate in comparison to discretionary foods; indicative of a moderate diet quality. Lack of time for meal preparation, convenience, low cost and taste were the reasons for established eating habits. Vast availability of foods as well as cultural values around food consumption were reasons contributing to increased food intake at social occasions.
Keywords: Obesity, New Zealand; Pacific Islanders, New Zealand; Young Pacific Islanders; Young people's nutrition; Pacific youth; Pacific youth eating habits